The Michigan prisoner reentry initiative: An examination of a statewide reentry program - Corwin, Michelle Lynn (2008)
The concept of prisoner reentry has only recently sparked a significant interest in the field of criminology and criminal justice; however, it is blatantly apparent that attention to the subject is not only needed but necessary. Each day men and women are sentenced to serve terms in prison systems throughout the country. Simultaneously, each day men and women are released from prison to reintegrate back into society. With the rising incarceration rates and rising release rates, it became clear that the United States has a difficult dilemma. Thus, attention to concepts that help in addressing such dilemmas, like prisoner reentry, became popular. This paper explores a prisoner reentry program designed to assist the State of Michigan in its battle towards addressing its prison problem. The Michigan Prisoner Reentry Initiative (MPRI) is a statewide initiative developed to reduce the rising incarceration rates in Michigan prison systems and assist those inmates returning home after being released. The information utilized was obtained from the current literature on prisoner reentry and the MPRI program. Also, methods such as participant observation and examinations of official documentations pertaining to the Michigan correctional systems was used to support the overall findings of this paper. The MPRI program is a step in the right direction for the State of Michigan and will prove to be a critical piece of solving the dilemma of reducing crime, incarceration rates, increasing public safety and assisting individuals released from prison to lead a law-abiding successful life outside of prison